A prospective evaluation of nice guidance on urinary tract infection in children under 5 years of age. (24th May 2012) - Lunn, A; Halliday, K; Broderick, N; Boswell, T; Smith, S; Watson, AR; Avery, A
Abstract : Aims: NICE guidance (2007) on urinary tract infection (UTI) included recommendations for fewer routine investigations in children over 6 months of age unless presenting with an atypical or recurrent UTI. The aim of our study was to prospectively assess whether children with risk factors for chronic kidney disease were identified using this selected approach in comparison to a universal ultrasound scan (USS) in children under 5 years of age following first presentation with a UTI. Methods: All positive urine cultures in children under 5 years of age requested by general practitioners or following hospital attendance from March 2009 until August 2011 were identified in our microbiology laboratory. Patients were excluded if there was prior imaging of the renal tract or if symptoms were not consistent with a UTI. Eligible patients were consented, reviewed and data were collected on demographics, family history, presenting features of the UTI and examination findings. Patients were classified according to the NICE criteria as NE (NICE eligible for investigation) or NN (not NICE eligible for investigation). An USS was performed in all children by a consultant paediatric radiologist blinded to the NICE classification of the patient. Results: 203 patients were deemed eligible and 197 patients (median age 3.4 years, 162 (82%) female) completed the study. In 13 (6.6%) patients, investigations were abnormal. In 60 NE patients 9 (18%) had radiological abnormalities compared with 4 (3%) of 137 NN patients (p=0.003, Fisher's exact test). Combining radiological and clinical assessment, to date 6 of 9 NE and 1 of 4 NN require long term renal assessment. Conclusion: Adherence to NICE guidance would have resulted in performing 137 fewer US scans and would have resulted in 4 fewer patients with renal tract abnormalities being identified. The long term outcomes need to be assessed but this study would suggest that applying NICE guidance to children under 5 years of age following a UTI will identify the majority of patients with significant renal tract abnormalities.